1991
DOI: 10.1002/ange.19911030631
|View full text |Cite
|
Sign up to set email alerts
|

Dichloro(pentamethylcyclopentadienyl)ruthenium ‐ neuartige Dichotomie einer Molekülstruktur

Abstract: Norhcv-t KIUfl. Lnrs Wiwr?iutin. Ulli Englut und GcvAurd E. Hcrherich Die Titelverbindung [(Cp*RuCI, ),I, (Cp* = $-C,Me,) I I t . ' I, 1st ein vielverwendetes Reagens fur die Herstellung von Cp*Ru-Sandwich-und insbesondere Halbsandwich-Verbindunger~[~-'I. Obgleich die Loslichkeit des Komplexes in halogenierten Kohlenwasserstoffen und die osmometrische Molmassenbestimmung in Chloroform[hh1 gegen das Vorliegen eines Polymers sprechen. wird die Verbindung durchgehend als solches angesehen[81. Wir berichten iiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
6
7
0
Order By: Relevance
“…Based on the characterization of three distinct isomers in the solid state, we decided to determine if the three structures exist in solution as well. [30] All data are consistent with the solution and solid-state structures being very similar. Since substitution of the methyl group on the thioether with a phenyl ring reduces the electron richness of the thioether, [6] this ligand should favor an "open" monodentate coordination mode.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Based on the characterization of three distinct isomers in the solid state, we decided to determine if the three structures exist in solution as well. [30] All data are consistent with the solution and solid-state structures being very similar. Since substitution of the methyl group on the thioether with a phenyl ring reduces the electron richness of the thioether, [6] this ligand should favor an "open" monodentate coordination mode.…”
supporting
confidence: 78%
“…[30] All data are consistent with the solution and solid-state structures being very similar. [30] The solid-state structure of 4 b showed a square-planar nickel center, much like 4 a, with two equivalents of N-bound SCN À ligands and two equivalents of the non-chelating phosphine each arranged in a trans configuration. Importantly, the room temperature 31 P{ 1 H} NMR spectrum of 4 a in CD 2 Cl 2 exhibits a broad resonance at d = 10.9 ppm, which sharpens with decreasing temperature (Supporting Information, Figure S1 B), consistent with a monodentate coordination mode for the phosphine ligand.…”
supporting
confidence: 78%
“…Indeed, complex 4 a was synthesized from a complex (3 a) prepared from NiCl 2 ·6 H 2 O and two equivalents of Ph 2 PCH 2 CH 2 SPh under similar conditions to those used to prepare 2 a-c (see the Supporting Information). As well as being characterized in the solid state by a single-crystal X-ray diffraction study (Figure 2 a) [30] All data are consistent with the solution and solid-state structures being very similar. [28,29] The solid-state structure of 4 a consists of a square-planar nickel center with two equivalents of N-bound SCN À ligands and two equivalents of P-bound monodentate P,S À Ph ligands arranged in trans configurations.…”
supporting
confidence: 78%
“…As in the case of 4 a, a single-crystal X-ray diffraction study of 4 b and 31 P{ 1 H}, 1 H, and 13 C{ 1 H} NMR spectroscopy indicated similar structures in solution and the solid state (Figure 2 b). [30] The solid-state structure of 4 b showed a square-planar nickel center, much like 4 a, with two equivalents of N-bound SCN À ligands and two equivalents of the non-chelating phosphine each arranged in a trans configuration. Significantly, room-temperature 31 P{ 1 H} NMR spectroscopy of 4 b in CD 2 Cl 2 showed a single sharp resonance at d = 16.7 ppm that remains unchanged with decreasing temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation